Prevention of Proximal Junctional Kyphosis After Posterior Surgery of Scheuermann Kyphosis: An Operative Technique. Issue 2 (March 2015) - Yanik, Hakan S.; Ketenci, Ismail E.; Polat, Atilla; Ulusoy, Ayhan; Deniz, Gokmen; Kose, Ozkan; Erdem, Sevki
Abstract : Study Design: A prospective randomized study. Objective: To introduce an operative technique that prevents proximal junctional kyphosis (PJK) in Scheuermann disease after a segmental posterior spinal instrumentation and fusion. Summary of Background Data: PJK is the progression of kyphotic deformity at the proximal end of a construct >10 degrees, and it can be seen up to 30% after posterior Scheuermann kyphosis surgery. After posterior fusion the biomechanics of the spine changes and the loss of motion at the fused levels is compensated by increased motion at other unfused segments. As a result significant amount of additional force is placed on the proximal junction. With our operative technique, we aimed to have a smooth passage from rigid to mobile segments and to decrease the stress on proximal junction during cantilever reduction to prevent PJK. Methods: A total of 60 consecutive patients (mean age: 18.27±3.19, male/female: 28/32) who were surgically treated for Scheuermann kyphosis in our institution were recruited into this study and were prospectively evaluated. Patients were divided into 2 groups according to upper-most screw fixation technique. In group 1, a standard screw insertion technique was used (ST group). The technique was modified in group 2 (MT group), leaving 2 threads out of the posterior cortex. There were 29 patients in group 1 (ST) and 31 patients in group 2 (MT). Patients had an average follow-up time of 24.2 months (range, 19–48 mo). Evaluated radiographic parameters were preoperative and postoperative kyphosis angle, and proximal junctional angle (PJA) at last visit. PJA was defined as the angle between the caudal endplate of the upper instrumented vertebra and the cephalad endplate of 2 suprajacent vertebrae above the upper instrumented vertebra. PJA exceeding 10 degrees was accepted as PJK. Quality of life measurement was assessed preoperatively and postoperatively with SF-36 questionnaire. Results: Correction amounts in ST group and MT group were 46.8% and 43.7%, respectively, which was statistically insignificant. The mean PJA was 8.08±2.96 degrees and 4.44±1.55 degrees in ST and MT groups, respectively, which demonstrated a statistically significant difference ( P =0.001). Five patients in ST group had a PJA exceeding 10 degrees (PJK), whereas PJK was not seen in MT group ( P =0.022). The improvement in physical component summary of SF-36 was significantly better in MT group; however, mental component summary was similar in both groups. Conclusions: This study introduces a new technique that may have an effect in preventing PJK. Our results seem to be satisfactory, but additional studies with more patients and longer follow-up times are needed to further delineate the feasibility of this technique.